The device ID of the mechanical characteristics of the relay - Гуз, Ю.Т.; Єнчев, С.В.; Сильнягін, А.О.; Прохоренко, І.В.; Мазур, Т.А. (Proceedings of National Aviation University (archive), 2009)
The method and the block diagram of the device are developed for identification to the mechanical characteristic of the relay of a direct current, which magnetic system nonlinear.